2015
DOI: 10.1149/2.0621512jes
|View full text |Cite
|
Sign up to set email alerts
|

Ion Distributions at Electrified Water-Organic Interfaces: PB-PMF Calculations and Impedance Spectroscopy Measurements

Abstract: The interface between two immiscible electrolyte solutions consisting of alkali chlorides in water and the organic electrolyte BTPPATPFB in 1,2-dichloroethane is characterized with X-ray reflectivity, interfacial tension and impedance spectroscopy measurements over a range of applied voltage between the bulk solutions. X-ray reflectivity probes the interfacial ion distribution on the sub-nanometer length scale, whereas interfacial tension and impedance spectroscopy characterize quantities such as interfacial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 54 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…The high frequency behaviour observed in EIS spectra at a polarised ITIES has been attributed to stray capacitance and resistance associated with the parasitic coupling of the reference and counter electrodes, as well as to the resistance of the bulk solution [24,30]. Wiles et al [15] suggested that the high frequency behaviour comes from artefacts due to both the cell and reference arm resistances of the organic phase, and stray capacitances of the potentiostat and leads.…”
Section: Resultsmentioning
confidence: 99%
“…The high frequency behaviour observed in EIS spectra at a polarised ITIES has been attributed to stray capacitance and resistance associated with the parasitic coupling of the reference and counter electrodes, as well as to the resistance of the bulk solution [24,30]. Wiles et al [15] suggested that the high frequency behaviour comes from artefacts due to both the cell and reference arm resistances of the organic phase, and stray capacitances of the potentiostat and leads.…”
Section: Resultsmentioning
confidence: 99%
“…Mobile ions rearrange so as to screen the charge at the electrode surface, thus forming an electrical double layer (EDL) in this process. The EDL has great importance in biological, colloidal and polyelectrolyte sciences, [1][2][3][4][5] surface conductivity, 6 renewable energy systems, 7,8 new methods for oil recovery, 9 and in electrical double layer capacitors, a device that stores electrochemical energy through the EDL. 10,11 The electrode is often approximately described by a perfectly planar charged surface, but other geometries have also been taken into account.…”
Section: Introductionmentioning
confidence: 99%